Pengembangan Komik Berbasis Karakter pada Pembelajaran Pecahan di Kelas V SD - Syafitri, Julia; Sukmawarti, Sukmawarti (Indonesian Research Journal on Education, 2022)
The problem raised by the author in this study is that the use of interesting learning media on Fractions material is rarely used. And the use of learning media is still less varied for students, because the teacher only conveys material using learning media in the form of pictures in student textbooks. And rarely develop learning media in the form of character-based comics. Therefore, the author aims to determine the feasibility and produce character-based comic learning media in Mathematics learning with fractions for elementary school students. This research is a type of Research and Development (R&D) research with a 4D model developed by Thiagarajan (1974) which includes four steps: define, design, development and disseminate. But modified into a 3D model. The subjects in this study were material expert validators, media experts and teachers. The instrument used to collect data is a questionnaire. The questionnaire will be assessed by selecting "Yes" or "No". The data analysis method used is a qualitative descriptive analysis method. The media developed was validated by material experts, media experts and fifth grade teachers at SD Negeri 060788 Medan. The character-based comic media is produced through an assessment of the validation results by material experts, media experts and fifth grade teachers at SD Negeri 060788 Medan so it is very suitable for use for fifth grade elementary school students. Although there are some criticisms and suggestions from material and media experts, such as improving the number writers, and media according to their characters, which have been revised by the authors, so it can be concluded that character-based comics media in fractional learning are very suitable to be used as learning media in the teaching and learning process.